SOSIALISASI TERAPI BRAIN GYM PADA ANAK USIA PRASEKOLAH ( 4 TAHUN ) UNTUK MENURUNKAN TINGKAT KECEMASAN AKIBAT HOSPITALISASI DI RUANG RAWAMERTA RSUD KARAWANG - Wirdan Fauzi Rahman,; Yuli Erlina,; Siva Salsabila, (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2024)
Hospitalization is a stressful experience for preschool-aged children because they are unable to fully understand their illness and the unfamiliar hospital environment. This often leads to anxiety, fear, and resistance to medical procedures. One non-pharmacological approach that can help reduce children's anxiety is Brain Gym therapy, a series of simple body movements designed to balance right and left brain function and promote relaxation. This community service activity aims to improve the knowledge and skills of nurses and parents in implementing Brain Gym therapy for preschool children (4 years old) to reduce anxiety caused by hospitalization. The activity method involved outreach, live demonstrations, and practical assistance for participants, consisting of pediatric nurses and patient companions in the Rawamerta Ward at Karawang Regional Hospital. Results showed an 85% increase in participants' knowledge after the outreach, and children appeared more relaxed and cooperative during medical procedures after Brain Gym implementation. This activity received a positive response from nurses and parents. Conclusion: Brain Gym therapy outreach effectively increased the understanding and skills of nurses and parents in reducing anxiety caused by hospitalization in preschool-aged children